(untitled) (American Journal of Islam and Society, 2000)
From Wealth to Power is a study in the social and historical dynamics contributing to the rise and fall of essential actors in the international system. It attempts to join history with social sciences theory in order to shed light on broad theoretical topics in world politics, such as the rise of new great powers. In so doing it seeks to add to the body of scholarship that combined the study of state structure with traditional international relations theory. The particular focus is on the expansive rise of the United States, not only to world prominence, but also as a modem state. American foreign policy during the period 1865-1908 is examined in light of changes in the state structure along the four major variables- scope, autonomy, coherence, and capacity (p. 40)- touching upon that country’s domestic and administrative development. The first of the six chapters of the book poses the main questions that Zakaria attempts to address: ’’What turns rich nations into ’great powers’?’’ "Why, as states grow increasingly wealthy, do they build large annies, entangle themselves in politics beyond their borders, and seek international influence?" "What factors speed or retard the translation of material resources into political interests?" (p. 3) and finally, "Under what conditions do states expand their political interests abroad?" (p. 18). Such questions visualize, on the one hand, a strong and direct correlation between great powers’ economic rise and fall and their growth or decline. Anomalies, on the other hand, are explained as a "Dutch disease," or the malady that does not allow "a nation of unequalled individual prosperity and commercial prowess from remaining a state of great influence and power" (pp. 4-5). The latter, Zakaria claims, was an American affliction during the second half of the nineteenth century. This was particularly true during the relatively long period of nonexpansion and isolation following the Civil War (1860–64). Despite a tremendous increase in wealth, productivity, and power, it was not until the 1890s that the US began expanding again. Zakaria considers this to be an aberration, reflecting a "highly unusual gap between power and interests" that lasted for some thirty years (p. 5). An explanation, according to him, would not only require a full historical account, but also "first-cut theories" which clarify national behavior (p. 8) ...